Policy Concept and Designs of Oil and Gas Governance in Indonesia’s Oil Companies - Chandranegara, Ibnu Sina; Hoesein, Zainal Arifin (International Journal of Energy Economics and Policy, 2019)
Indonesia’s oil and gas governance has been specified in certain laws. The first oil and gas law was Emergency Law No. 44 of 1960. This law was changed to Law No. 8 of 1971 which gave a dual function, namely to Pertamina National Oil Company (NOC), as an operator and regulator. Meanwhile, the function of policy making was carried out by the government. These two functions are known as “two feet.” Furthermore, with the promulgation of the Oil and Gas Law No. 22 of 2001, there was a separation of regulatory functions by Pertamina and giving them to state institutions known as BP Migas. The agency was later converted into two different institutions, SKK Migas for regulating upstream oil and gas and BPH Migas for downstream regulation. These functions are known as ‘three feet’. However, the Oil and Gas Law No. 22 of 2001 received a lot of criticism, because this law was considered too liberal and put Pertamina as a NOC to compete openly with the International Oil Company (IOC) which was considered to have more good advantages in technology, capital, and risk management. The existing Oil and Gas Law has caused prolonged stagnation in the national oil and gas industry, and reduced the performance of this strategic industry in terms of lifting, exploration, exploitation and oil production. This study is intended to provide a description regarding the various design concepts of oil and gas law governance by referring to the oil and gas management and performance models in various countries and IOC. Furthermore, this study empirically offers a comparison of the NOC model in managing oil and gas, and the advantages and disadvantages of institutional selection over the oil and gas administration Keywords: Energy Policy, Oil Sector Performance, National Oil Company, Governance JEL Classifications: Q43, O13, O38 DOI: https://doi.org/10.32479/ijeep.7458